Education for Housewives in Managing Inorganic Waste through Pocket Books in Lamongan Regency - Dian Mawarni; Anindya Hapsari; Tika Dwi Tama; Muhammad Al Irsyad; Avida Shafa Tiffani; Putri Nurika Dewi; Anis Yunita (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
The inorganic waste from household activities in Kudikan Village, Sekaran District, Lamongan Regency is quite high but its management is still not appropriate. Community service activities aim to strengthen the capacity of the community in inorganic waste management from domestic. An offline education involves 50 housewives from Posyandu participants. A pictorial pocket book on inorganic waste and how to manage it was developed as an educational media. The majority of housewives (82%) have good knowledge while the rest are categorized as sufficient (14%), and less (4%). Most of the housewives (92%) have a good attitude while others are quite moderate (4%). At the end of the education session, the pocket books are given to the housewives to study independently. After receiving education, housewives are expected to be able to properly implement inorganic waste management in the household environment so that the production of inorganic waste is reduced.